Nurse staffing and the work environment linked to readmissions among older adults following elective total hip and knee replacement - Lasater, Karen B. (Int J Qual Health Care, 2016)
OBJECTIVE: To examine the effect of nurse staffing and the work environment on 10- and 30-day unplanned readmissions for US Medicare patients following elective total hip and knee replacement. DESIGN: A cross-sectional analysis of secondary data. SETTING: Acute care hospitals in California, Florida, New Jersey and Pennsylvania, during 2006. PARTICIPANTS: Medicare patients (n = 112 017) admitted to an acute care hospital for an elective total hip or knee replacement. MAIN OUTCOME MEASURES: The adjusted odds ratio (OR) of experiencing an unplanned readmission within 10 and 30 days of discharge following an elective total hip or knee replacement. RESULTS: Our sample included 112 017 Medicare patients in 495 hospitals. Nearly 6% of the patients were readmitted within 30 days; more than half of whom were rehospitalized within 10 days. Adjusted for patient and hospital characteristics, patients had 8% higher odds of 30-day readmission and 12% higher odds of 10-day readmission, for each additional patient per nurse. Patients cared for in the best work environments had 12% lower odds of 30-day readmission. CONCLUSIONS: Readmission outcomes following major joint replacement are associated with hospital nursing care. Attention to nurse work conditions may be central to improving readmissions in this postoperative Medicare population.